Who Moves the Malaysian Stock Marketâ the U.S. or Japan?: Empirical Evidence from the Pre-, During, and Post-1997 Asian Financial Crisis - Mohd. Yusof, Rosylin; Abd. Majid, M. Shabri (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This paper examines long run co-movements between Malaysian stock market and the two largest stock markets in the world: the U.S. and Japan. By employing time-series analysis, i.e., cointegration, variance decompositions, and impulse response functions, the paper seeks to investigate which market actually leads the Malaysian stock market before, during, and after the 1997 Asian financial crisis periods. The results indicate that there is a co-movement of these markets only in the post crisis period. The Japanese stock market is found to significantly move the Malaysian stock market compared to U.S. stock market for the post-crisis period. At the same time, there seems to be a growing proportion of bilateral trade between Malaysia and Japan during the mentioned period. This finding seems to be consistent with the view that the stronger the bilateral trade ties between two countries, the higher the degree of co-movements (Masih and Masih 1999; Bracker et al. 1999; Pretorius 2002; Ibrahim 2003; Kearney and Lucey 2004). Our finding implies that the opportunities of gaining abnormal profits through investment diversification during the post-crisis period in the Malaysian and Japanese stock markets are diminishing as the markets move towards a greater integration. This further implies that any development in the Japanese economy has to be taken into consideration by the Malaysian government in designing policies pertaining to Malaysian stock market.